Genetic variation in bone morphogenetic proteins and breast cancer risk in hispanic and non‐hispanic white women: The breast cancer health disparities study. Issue 12 (13th December 2012) - Slattery, Martha L.; John, Esther M.; Torres‐Mejia, Gabriela; Herrick, Jennifer S.; Giuliano, Anna R.; Baumgartner, Kathy B.; Hines, Lisa M.; Wolff, Roger K.
Abstract Bone morphogenetic proteins (BMP) are thought to be important in breast cancer promotion and progression. We evaluated genetic variation in BMP‐related genes and breast cancer risk among Hispanic (2, 111 cases, 2, 597 controls) and non‐Hispanic White (NHW) (1, 481 cases, 1, 586 controls) women who participated in the 4‐Corner's Breast Cancer Study, the Mexico Breast Cancer Study and the San Francisco Bay Area Breast Cancer Study. BMP genes and their receptors evaluated include ACVR1, AVCR2A, ACVR2B, ACVRL1, BMP1, BMP2, BMP4, BMP6, BMP7, BMPR1A, BMPR1B, BMPR2, MSTN and GDF10. Additionally, 104 ancestral informative markers were assessed to discriminate between European and native American ancestry. The importance of estrogen on BMP‐related associations was suggested through unique associations by menopausal status and estrogen (ER) and progesterone (PR) receptor status of tumors. After adjustment for multiple comparisons ACVR1 (8 SNPs) was modestly associated with ER+PR+ tumors [odds ratios (ORs) between 1.18 and 1.39 padj < 0.05]. ACVR1 (3 SNPs) and BMP4 (3 SNPs) were associated with ER+PR− tumors (ORs 0.59–2.07; padj < 0.05). BMPR2 was associated with ER−PR+ tumors (OR 4.20; 95% CI 1.62, 10.91; padj < 0.05) as was GDF10 (2 SNPs; ORs 3.62 and 3.85; padj < 0.05). After adjustment for multiple comparisons several SNPs remained associated with ER−PR− tumors (padj < 0.05) including ACVR1BMP4 and GDF10 (ORs between 0.53 and 2.12). Differences in association also were observed by percentage of native ancestry and menopausal status. Results support the hypothesis that genetic variation in BMPs is associated with breast cancer in this admixed population.